True political representation of disadvantaged neighbourhoods? - Filip de Maesschalck (Brussels Studies)
This article examines where Brussels parliamentary members live, looking at the evolution of this phenomenon over the past 20 years. The central question focuses on whether different neighbourhoods within the Brussels Capital Region also experienced a different pattern of representation throughout this period. The analysis shows that the centrally located poor neighbourhoods had little if any representation at the end of the 1980s, but that this underrepresentation gradually decreased and has now just about completely disappeared. The increasing number of parliamentary members of non-European origin has played a role in this evolution, but other parliamentary members are also increasingly living in centrally located neighbourhoods. Furthermore, historical anchoring in certain areas continues to play a role. There are major differences between the political ideologies which broadly follow a left-right continuum, and which are also increasing. The increasing representation of the central urban neighbourhoods simultaneously creates opportunities and challenges for urban policy. Although a lack of policy interest in these neighbourhoods is becoming increasingly unlikley, this does not necessarily go hand in hand with an increase in the amount of attention paid to the current residents within these neighbourhoods.